РОЛЬ И МЕСТО БЕРЕЖЛИВЫХ ТЕХНОЛОГИЙ ПРИ ОПТИМИЗАЦИИ ОКАЗАНИЯ НЕОТЛОЖНОЙ МЕДИЦИНСКОЙ ПОМОЩИ В ПЕРВИЧНОМ ЗВЕНЕ - Прудникова, Мария Дмитриевна; Аль-Харес, Милад Мтанусович; Панкратова, Полина Андреевна; Давлетова, Лола Айдаровна; Гавщук, Ольга Владимировна; Близнякова, Дарья Сергеевна (FORCIPE, 2022)